Angara interconnect makes GPU-based Desmos supercomputer an efficient tool for molecular dynamics calculations. (May 2019) - Stegailov, Vladimir; Dlinnova, Ekaterina; Ismagilov, Timur; Khalilov, Mikhail; Kondratyuk, Nikolay; Makagon, Dmitry; Semenov, Alexander; Simonov, Alexei; Smirnov, Grigory; Timofeev, Alexey
In this article, we describe the Desmos supercomputer that consists of 32 hybrid nodes connected by a low-latency high-bandwidth Angara interconnect with torus topology. This supercomputer is aimed at cost-effective classical molecular dynamics calculations. Desmos serves as a test bed for the Angara interconnect that supports 3-D and 4-D torus network topologies and verifies its ability to unite massively parallel programming systems speeding-up effectively message-passing interface (MPI)-based applications. We describe the Angara interconnect presenting typical MPI benchmarks. Desmos benchmarks results for GROMACS, LAMMPS, VASP and CP2K are compared with the data for other high-performance computing (HPC) systems. Also, we consider the job scheduling statistics for several months of Desmos deployment.